The Effect Of Company Size, Financial Stability And External Pressure On Financial Statement Fraud - Jumali, Ahmad; Muniroh, Hetty (Accounting Global Journal, 2023)
The purpose of the research to be conducted is to determine the effect of to company size, financial soundness, and external pressure on the financial statement fraud in food and beverage companies. Researchers used the documentation method, the entire population of 16 food and beverage companies listed on the Indonesia Stock Exchange after being outliers became 14 companies, 3 years of research from 2019-2021. Data analysis techniques using the classical assumption test, descriptive statistics, multiple linear regression analysis and test the coefficient of determination. The results of this study, which employs several linear regression analytic techniques, demonstrate that the factors of company size, financial soundness and outside pressure have little bearing on financial statement fraud.